The Influence of Perceived Organizational Support and Perceived Discrimination on Job Satisfaction : (Study on CV. Indo Samudra dan PT. Lumbung Nusantara Nastiti) - Yu Alam; Habibullah Jimad (International Journal of Economics and Management Sciences, 2024)
This study aims to determine the effect of perceived organizational support on job satisfaction of employees of CV Indo Samudra and PT Lumbung Nusantara Nastiti, and to determine the perception of discrimination on job satisfaction of employees of CV Indo Samudra and PT Lumbung Nusantara Nastiti. The type of research used in this study uses quantitative research, using associative methods. The population in this study amounted to 158 and the sample used was 135 employees of CV Indo Samudra and PT Lumbung Nusantara Nastiti with the sampling technique, namely proportionate stratified random sampling. Data analysis using multiple linear regression analysis and hypothesis testing, namely the T test. The results of the T test test show that perceived organizational support has a significant positive effect on job satisfaction of employees of CV Indo Samudra and PT Lumbung Nusantara Nastiti and perceived discrimination has a significant negative effect on job satisfaction.